Novel polythiophene derivative for dual-channel cell imaging. Issue 30 (3rd June 2019) - Wang, Fengyan; Xia, Huiyun; Pu, Siyu; Yan, Ni; Song, Jiale; Tian, Yefei; Wei, Junji; Yan, Luke
Abstract : PT-OH-PPR has good optical properties, good water solubility and low cytotoxicity, and could be used as a dual-channel cell imaging material. Abstract : Fluorescent materials play an extremely important role in understanding the microbiological world. New fluorescent materials which have good photophysical properties, low cytotoxicity, and multi-channel fluorescent imaging capability are still urgently needed, even though many kinds of fluorescent materials have already been synthesized. In this work, a new polythiophene derivative (PT-OH-PPR) modified with a porphyrin group in its side chain was designed and fabricated through FeCl3 oxidative polymerization. The obtained PT-OH-PPR has wide absorption and emission spectral range, good water solubility and low cytotoxicity. Importantly it could be enriched in the cytoplasm of A549 cells and be excited by two excitation wavelengths (488 nm and 559 nm), which provides a promising application in dual-channel cell imaging.